Construções com "ficar" em português e suas correspondentes em italiano - Almeida, Andressa Spinosa (2024)
Based on a cognitive-functional approach, the central aim of this work is to study Italian constructions corresponding to constructions with ficar, in particular, the construction [ficar + infinite verb form] in Portuguese, comparing the semantic-discursive functions of these constructions taken from short stories by the writer Clarice Lispector. To this end, it will analyse formal, semantic and pragmatic categories in Clarice's short stories in Portuguese and their respective Italian translations, such as: the constructional pattern, the nature of the auxiliary in Italian; the tense and verbal mode of the auxiliary; the animacy of the SN subject, as well as its informational status and semantic role; the aspectual notion, the degree of transitivity and the discursive relevance of the construction. Analysing 108 constructions with ficar in parallel with the Italian translations led to the following results: (a) the most common constructional pattern in both languages is [verb + adjective], with only 32 constructions in which the verb ficar appears in an infinite form; (b) the verb ficar is translated in Italian predominantly by rimanere, which, like ficar, takes on both a permissive and incoative value; (c) the indicative mood and the remote past tense, equivalent to the preterite perfect in Portuguese, were more frequent; (d) there is a predominance of constructions with an animate subject, in the role of patient and given informational status; (e) there is a predominance of dynamic, uncontrolled and telic states of affairs; (f) the constructions were similarly divided between the permissive and incoative aspects, with some cases of simultaneous expression of both aspects, and showed a degree of medial transitivity, assuming the discursive prominence of Figure and Background, also in a balanced way. The use of different ways of translating the verb ficar in Portuguese in periphrastic constructions [ficar + Vdo/Vndo,/ a + Vinf] seems to be primarily due to the aspectual value of the construction and the type of change encoded, whether of physical or mental state, or of property. These results, although limited by the small sample size, may shed light on the functioning of the verb ficar in Portuguese, in parallel with its Italian counterparts, contributing to the description of the two languages and to the teaching of Italian as an L2, especially to Portuguese speakers.